Analysis Of The Effect Of Exchange Value, Inflation Level, SBI Interest Rate And Hang Seng Index For Joint Stock Price Index In Indonesia Stock Exchange (Study On IDX 2016 - 2019) - Rusdi Hidayat Nugroho, Sonja Andarini, Riko Setya Wijaya, Budi Prabowo (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The driver of one country’s economy is capital markets, several factors that affect capital markets such as internal and external macroeconomics. the capital market conditions of a country are heavily influenced by various factors, namely internal and external macroeconomic conditions affecting the country. In this case, it aims to know and analyze the effect of rupiah on the exchange rate of the United States Dollar and, the inflation rate, bi-interest rate, and Hang Seng Index on the Stock Price Index (JCI) in the first quarter of -2019 Quarter IV, either partially or simultaneously. The data used is in the form of secondary data obtained through the website of Bank Indonesian and IDX. The data analysis method used is multiple linear regression analysis with a significance level of 0.05. This study concludes that in the 2016 quarter I -2019 Quarter IV, the Hang Seng Index partially has a significant effect on the JCI. in other ways the exchange rate of rupiah to the us dollar, bank indonesia interest rate, and inflation has no effect on JCI. In addition, it was found that the value of R-square is 84.7%. This means that 84.7% of all observations suggest that independent variables can explain variations in dependent variables, the remaining 15.3% (obtained from 100% - 84.7%) other factors not seen in the model or errors.